Vulnerability and resilience of living marine resources to the Deepwater Horizon oil spill: an overview - Murawski, Steven A.; Schwing, Patrick T.; Patterson, William F.; Sutton, Tracey T.; Montagna, Paul A.; Milligan, Rosanna J.; Joye, Samantha B.; Thomas, Len; Kilborn, Joshua P.; Paris, Claire B.; Faillettaz, Robin; Portnoy, David S.; et al. (Frontiers in Marine Science, 2023)
The 2010 Deepwater Horizon (DWH) oil well blowout in the Gulf of Mexico (GoM) was the largest and perhaps most consequential accidental marine oil spill in global history. This paper introduces a Research Topic consisting of four additional papers that: (1) assemble time series data for ecosystem components in regions impacted by the spill, and (2) interpret temporal changes related to the vulnerability of species and ecosystems to DWH and the ensuing resilience to perturbation. Time series abundance data for many taxa pre-date DWH, often by decades, thus allowing an assessment of population- and community-level impacts. We divided the north central GoM into four interconnected “ecotypes”: the coastal/nearshore, continental shelf, open-ocean pelagic and deep benthic. Key taxa in each ecotype were evaluated for their vulnerability to the circumstances of the DWH spill based on population overlap with oil, susceptibility to oil contamination, and other factors, as well their imputed resilience to population-level impacts, based on life history metrics, ecology and post-spill trajectories. Each taxon was scored as low, medium, or high for 13 vulnerability attributes and 11 resilience attributes to produce overall vulnerability and resilience scores, which themselves were also categorical (i.e., low, medium, or high). The resulting taxon-specific V-R scores provide important guidance on key species to consider and monitor in the event of future spills similar to DWH. Similar analyses may also guide resource allocation to collect baseline data on highly vulnerable taxa or those with low resilience potential in other ecosystems. For some species, even a decade of observation has been insufficient to document recovery given chronic, long-term exposure to DWH oil remaining in all ecotypes and because of impacts to the reproductive output of long-lived species. Due to the ongoing threats of deep-water blowouts, continued surveillance of populations affected by DWH is warranted to document long-term recovery or change in system state. The level of population monitoring in the open ocean and deep benthic ecotypes has historically been low and is inconsistent with the continued migration of the oil industry to the ultra-deep (≥1,500 m) where the majority of leasing, exploration, and production now occurs.